2017
DOI: 10.18203/2349-2902.isj20174101
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing of laparoscopic cholecystectomy after endoscopic retrograde cholangiopancreatography

Abstract: INTRODUCTIONSymptomatic cholelithiasis is a common gastrointestinal surgical entity having the complication of accumulation of gall stones. Although, therapeutic options are laparoscopic, endoscopic, percutaneous surgery and open traditional technique either through a combination of any of cited treatments or by conducting those in a step wise sequence to manage gallstones and common bile duct (CBD) stones, there is no clear consensus on the correct strategy.Obviously, endoscopic retrograde cholangiopancreatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 8 publications
(8 reference statements)
1
7
0
Order By: Relevance
“…In the current study, the mean hospital stay duration for group I patients was notably shorter than the mean hospital stay duration for group II patients (p<0.001). This finding mimics many kinds of literature such as Sahoo et al [23] studies in India and the El-Labban study in Egypt [24] which all reported that patients with earlier time intervals between ERCP and LC had shorter hospital stay duration than patients with later interval.…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, the mean hospital stay duration for group I patients was notably shorter than the mean hospital stay duration for group II patients (p<0.001). This finding mimics many kinds of literature such as Sahoo et al [23] studies in India and the El-Labban study in Egypt [24] which all reported that patients with earlier time intervals between ERCP and LC had shorter hospital stay duration than patients with later interval.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, there was no significant difference seen among demographic findings that correlate with the previous studies. 9 , 10 However, significant preoperative ultrasound finding was increased wall thickness in group II. 10 It was clearly observed that and seen consistent with our studies that the duration of surgery and hospital stay was significantly more in patients undergoing LC after an interval of 8 weeks.…”
Section: Discussionmentioning
confidence: 89%
“… 9 , 10 However, significant preoperative ultrasound finding was increased wall thickness in group II. 10 It was clearly observed that and seen consistent with our studies that the duration of surgery and hospital stay was significantly more in patients undergoing LC after an interval of 8 weeks. 9 11 Operative difficulty and grade of adhesions were significantly higher in cases undergoing surgery after a delayed period, and this observation is clearly supported by many studies.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations